Medical financial hardship among cancer survivors in the United States - Zheng, Zhiyuan; Jemal, Ahmedin; Han, Xuesong; Guy, Gery P.; Li, Chunyu; Davidoff, Amy J.; Banegas, Matthew P.; Ekwueme, Donatus U.; Yabroff, K. Robin (Cancer, 2019)
Background The current study examined medical financial hardship in cancer survivors and those without a cancer history in the United States. Methods The 2013 to 2016 National Health Interview Survey was used to identify cancer survivors (stratified by ages 18‐49 years [1424 survivors], ages 50‐64 years [2916 survivors], and ages ≥65 years [6014 survivors]) and individuals without a cancer history (ages 18‐64 years [66,951 individuals], ages 50‐64 years [31,741 individuals], and ages ≥65 years [25,744 individuals]). Medical financial hardship was categorized into 3 domains: 1) material (eg, problems paying medical bills); 2) psychological (eg, worrying about paying medical bills); and 3) behavioral (eg, delaying/forgoing care due to cost). Generalized ordinal logistic regressions were used to examine the associations between cancer history, hardship, and health insurance deductibles/health savings accounts (among privately insured cancer survivors aged 18‐64 years only). Results Compared with those without a cancer history, cancer survivors were more likely to report any material (ages 18‐49 years: 43.4% vs 30.1%; ages 50‐64 years: 32.8% vs 27.8%; and ages ≥65 years: 17.3% vs 14.7%), psychological (ages 18‐49 years: 53.5% vs 47.1%), and behavioral (ages 18‐49 years: 30.6% vs 21.8%; and ages 50‐64 years: 27.2% vs 23.4%) measure of financial hardship, and multiple domains of hardship (age groups 18‐49 years and 50‐64 years; all P < .01). Among privately insured survivors, having a high‐deductible health plan without a health savings account was found to be associated with greater hardship compared with having low‐deductible insurance. Conclusions Younger cancer survivors are particularly vulnerable to material, psychological, and behavioral medical financial hardship. Interventions designed to reduce financial hardship should consider multiple domains of hardship as well as insurance benefit design. Cancer survivors encounter greater medical financial hardship compared with individuals without a cancer history in material, psychological, and behavioral domains, with the greatest hardships observed in younger populations. Among privately insured survivors, having a high‐deductible health plan without a health savings account is associated with greater medical financial hardship.